Regnase-1 overexpression as a therapeutic approach of Marfan syndrome - Noormalal, Marie; Schmiedel, Nesrin; Bozoglu, Tarik; Matzen, Andrea; Hille, Susanne; Basha, Dima Ibrahim; Vijaya Shetty, Prithviraj Manohar; Wolf, Anja; Zaradzki, Marcin; Arif, Rawa; Pühler, Thomas; Lutter, Georg; et al. (Molecular therapy. Methods & clinical development, 2024)
Rupture or dissection of thoracic aortic aneurysms is still the leading cause of death for patients diagnosed with Marfan syndrome. Inflammation and matrix digestion regulated by matrix metalloproteases (MMPs) play a major role in the pathological remodeling of the aortic media. Regnase-1 is an endoribonuclease shown to cleave the mRNA of proinflammatory cytokines, such as interleukin-6. Considering the major anti-inflammatory effects of regnase-1, here, we aimed to determine whether adeno-associated virus (AAV)-mediated vascular overexpression of the protein could provide protection from the development and progression of aortic aneurysms in Marfan syndrome. The overexpression of regnase-1 resulted in a marked decrease in inflammatory parameters and elastin degradation in aortic smooth muscle cells in vitro. Intravenous injection of a vascular-targeted AAV vector resulted in the efficient transduction of the aortic wall and overexpression of regnase-1 in a murine model of Marfan syndrome, associated with lower circulating levels of proinflammatory cytokines and decreased MMP expression and activity. Regnase-1 overexpression strongly improved elastin architecture in the media and reduced aortic diameter at distinct locations. Therefore, AAV-mediated regnase-1 overexpression may represent a novel gene therapy approach for inhibiting aortic aneurysms in Marfan syndrome.
Gesehen am 12.08.2024